Caracterização de frutos e de mudas de mangabeira(Hancornia speciosa Gomes) de Goiás - VIEIRA, Muza do Carmo (2011)
Mangabeira (Hancornia speciosa) is a fruit tree, native to Brazil and found in various regions of the country, from the Coastal Plains and Southeast. We conducted this study in order to characterize fruits and seedlings in nursery and field mangabeira of different plants and natural areas of occurrence in the Cerrado of the State of Goiás ten areas were selected and each were chosen randomly plants were in full production. These plants were collected up to 12 fruits. Separating samples of five ripe fruit per plant are evaluated the following characteristics: weight, transversal and longitudinal directions, the total number of seeds and the total mass of seeds. Each pulped fruit and seeds washed and dried, separated samples per plant and a subsample of these two seeds were sown in separate tubes and for evaluation of emergency (%) and emergence speed index (ESI) (%). In the nursery, seedlings originated from seeds that were evaluated: length (cm) and number of air p sheets (NPF). Data were collected monthly for each offspring to the tenth evaluation. Ultimately, they separate, and these six plants, three samples per array seedlings were planted in the field at the School of Agronomy and Food Engineering - UFG and three in the Federal Institute Campus Urutaí Goiás-GO and underwent monthly assessments leading into account the diameter (mm) length (cm) and number of pair of sheets. Among matrices test was performed for average, maximum, minimum and coefficient of variation. Means were compared by Tukey test at 5% probabilidde. It was observed that the average fruit weight of mangabeira collection areas in the State of Goiás is 42.7 g, the emergence of the seeds began the 12th day after sowing (DAS), extending to 41; the mean emergence was 55.4% and the average number of days to emergence was 22.64 (DAS), seedlings in nurseries practically stabilize its growth between May and September. The average monthly rate of growth ranged from 0.1 cm (January-February) to 6.1 cm (September-October), with an average rate of 2.19 cm. In the field mangabeira presents a good early growth with monthly increase of 4.8 cm from January to February, 8.1 cm from February to March, closing at 2.1 cm from March to April of 2011 and average final growth of 3.75 cm, for the seedlings in Goiania. In Urutaí monthly increase was 1.0 cm in the months from February to March and - 5 cm from March to April of 2011, with an average of 0.5 cm of growth. It is suggested seedlings between 3 and 4 months to be taken to the field, so that development gains are sustained.